THE EFFECT OF MARKET ORIENTATION AND SERVICE INNOVATION ON MARKETING PERFORMANCE MEDIATED BY COMPETITIVE ADVANTAGE - Hendra, Hendra; Winoto Tj, Hery; Tecoalu, Melitina (CV. Radja Publika, 2022)
This study discusses market orientation and service innovation on marketing performance mediated by competitive advantage variables. The results of the research on the first hypothesis are an effect of market orientation on competitive advantage variables with a t-statistic of 6.767> 1.99 and a significance value of 0.000 <0.05. The second hypothesis in this study is that there is an effect of service innovation on the competitive advantage variable with t-statistic 2,227 > t-table 1.99 and a significance value of 0.026 <0.05. The third hypothesis in this study is that there is an effect of competitive advantage on the marketing performance variable with a t-statistic of 2.357 > 1.96 and a significance value of 0.010 < 0.05. The fourth hypothesis in this study is that there is an effect of market orientation on the marketing performance variable with t-statistic 3.126 > t-table 1.99 and a significance value of 0.002 <0.05. The fifth hypothesis in this study is that there is an effect of service innovation on the marketing performance variable with t-statistic 2,470 > t-table 1.99 and a significance value of 0.014 <0.05. The sixth hypothesis is that the competitive advantage variable can mediate the relationship between market orientation and marketing performance with t-statistic 2,209 > t-table 1.99 or p 0.028 <0.05. The seventh hypothesis is that the service innovation variable cannot mediate the relationship between market orientation and marketing performance with t-statistic 1.504 < t-table 1.99 or p 0.133>0.05.